Book Review: Empowering Women of Mohattari District: A Case Study of selected Village Development Committee - Karna, Sohan K (Tribhuvan University Journal, 2011)
Not necessary. Key words: Women Empowerment; Nepal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 165-167 Uploaded date: 29 April, 2011